2005
DOI: 10.1089/hum.2005.16.845
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antitumor Activity of Oncolytic Adenovirus Expressing mda-7/IL-24 for Colorectal Cancer

Abstract: It has been demonstrated that interleukin 24 (IL-24, also called melanoma differentiation associated gene 7) exerts antitumor activity. In this study, we investigated whether oncolytic adenovirus-mediated gene transfer of IL-24 could induce strong antitumor activity. A tumor-selective replicating adenovirus expressing IL-24 (ZD55-IL-24) was constructed by insertion of an IL-24 expression cassette into the ZD55 vector, which is based on deletion of the adenoviral E1B 55-kDa gene. ZD55-IL-24 could express substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
124
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 43 publications
2
124
0
Order By: Relevance
“…We previously have reported that ZD55-delivering therapeutic genes (for example TRAIL and IL-24) suppresses tumor growth and induces tumor cell apoptosis. 28,29 We speculate that the potency of ZD55 could be similarly improved by the expression of synthetic lethal shRNAs against endogenous antiapoptotic genes instead of expressing proapoptotic transgenes.…”
Section: Discussionmentioning
confidence: 99%
“…We previously have reported that ZD55-delivering therapeutic genes (for example TRAIL and IL-24) suppresses tumor growth and induces tumor cell apoptosis. 28,29 We speculate that the potency of ZD55 could be similarly improved by the expression of synthetic lethal shRNAs against endogenous antiapoptotic genes instead of expressing proapoptotic transgenes.…”
Section: Discussionmentioning
confidence: 99%
“…This ability to augment cell killing by the combinatorial approach involves enhanced expression of MDA-7/IL-24 protein and concomitant alterations in the levels of BCL-family proteins in tumor cells. Achieving a threshold level of MDA-7/IL-24 protein appears critical for the induction of apoptosis by this novel cytokine, as recently emphasized using a conditionally replication-competent adenovirus to deliver MDA-7/IL-24 to human colorectal cancer xenografts in nude mice, which resulted in significant activity in curing animals of tumors and prolonging their survival (Zhao et al, 2005). The levels of expression of mda-7/IL-24 mRNA and protein resulting from delivery by the replicating virus greatly exceeded that of the non-replicating adenovirus in colorectal cancer cells, which demonstrated a less dramatic antitumor effect (Zhao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Achieving a threshold level of MDA-7/IL-24 protein appears critical for the induction of apoptosis by this novel cytokine, as recently emphasized using a conditionally replication-competent adenovirus to deliver MDA-7/IL-24 to human colorectal cancer xenografts in nude mice, which resulted in significant activity in curing animals of tumors and prolonging their survival (Zhao et al, 2005). The levels of expression of mda-7/IL-24 mRNA and protein resulting from delivery by the replicating virus greatly exceeded that of the non-replicating adenovirus in colorectal cancer cells, which demonstrated a less dramatic antitumor effect (Zhao et al, 2005). In these contexts, approaches that augment the achievable level of MDA-7/IL-24 protein in cancer cells may prove beneficial in enhancing the antitumor activity of mda-7/IL-24.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ZD55-IL-24 on growth suppression and apoptosis induction was found to be more significant than that of Ad-IL-24 in vitro. 20 Similarly, the animal tumor model studies also showed that antitumor efficacy of ZD55-IL-24 was much better than that of Ad-IL-24.…”
Section: Introductionmentioning
confidence: 92%